Perception study on multiple active learning techniques for telecommunication courses in Universiti Kebangsaan Malaysia - Asma’ Abu-Samah,; Nor Fadzilah Abdullah,; Mohd Fais Mansor,; Rosdiadee Nordin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Active learning is a 3-ways approach of teaching-learning in which lecturers and students engage in learning activities by using alternative methods such as writing exercises, educational games, problem-solving, reaction-viewing systems, debates, class discussions, and electronic media use. Although there is evidence to support the effectiveness of active learning strategies, the implementation of different techniques in higher learning programs is minimal. This study aimed to evaluate the perception of active learning from students exposed to the designed activities in three courses at the Department of Electrical, Electronics and Systems, Faculty of Engineering and Architecture, UKM. The three courses were KKKT3243 (Communication Devices), KKKT4133 (Communication Data and Computer Networks), and KKKT4193 (Radio and Satellite Communication). Evaluation using a questionnaire involved 27 student respondents from Years 3 and 4. In these courses, a number of complex topics were presented using various active learning techniques involving teaching materials based on the needs of the current telecommunications industry. The design also includes collaborative learning using media such as Google Drive and iFolio, a UKM learning management system. Questionnaire studies reported that students think they learn better and can relate theory and practice easily and quickly. Students, however, reckoned that the main obstacle to active learning was that lecturers needed more preparation and a lack of adequate infrastructure.